The Views of Students Related to Compassionate Love and Compassionate Love Education Course after Taking Compassionate Love Education Course - Şeyma Şahin; Burcu Ökmen; Abdurrahman Kılıç (Anı Publishing, 2019)
The aim of this study is to investigate the views of students about compassionate love and Compassionate Love Education after the elective course of Compassionate Love Education. The research was carried out within the scope of the "phenomenology" of qualitative research patterns. The study group consists of third year undergraduate students who take selective Compassionate Love Education course at a state university during the fall semester of the 2017-2018 academic year. Document review was used as data collection method. The documents are the evaluation articles of the students. In the analysis of the data, content analysis method was used. The results of the self-evaluation of the students after the lesson show that most of the students started to question their opinions about the concept of compassionate love and that their definition of compassionate love and their approach to the concept of compassionate love changed. After course, students generally stated that they were satisfied with course, that they thought it was beneficial, that it gave their life the awareness about compassionate love, and that it gave them different perspectives on compassionate love. In line with the results of the research various suggestions have been developed such that the right understanding of compassionate love for the students starting from pre-school should be created and course of Compassionate Love Education should be included in curriculums at the associate and undergraduate level as an elective course.